2013
DOI: 10.1111/1750-3841.12248
|View full text |Cite
|
Sign up to set email alerts
|

Development of Formulations and Processes to Incorporate Wax Oleogels in Ice Cream

Abstract: The objective of this study was to investigate the influence of emulsifiers, waxes, fat concentration, and processing conditions on the application of wax oleogel to replace solid fat content and create optimal fat structure in ice cream. Ice creams with 10% or 15% fat were formulated with rice bran wax (RBW), candelilla wax (CDW), or carnauba wax (CBW) oleogels, containing 10% wax and 90% high-oleic sunflower oil. The ice creams were produced using batch or continuous freezing processes. Transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Oleogels have been studied for over 10 years as healthy replacements for trans‐ fats since they can be formulated with vegetable oils with no trans‐ fats and low levels of saturated fatty acids (Co & Marangoni, ; Pernetti, van Malssen, Flöter, & Bot, ). Specific application includes the use of oleogels to replace solid fat in ice cream, frankfurters, and baked products (Calligaris, Manzocco, Valoppi, & Nicoli, ; Zetzl, Marangoni, & Barbut, ; Zulim Botega, Marangoni, Smith, & Goff, ). Oleogels are structured oil systems that can be defined as semisolid materials obtained by entrapping liquid oil into a three‐dimensional network.…”
Section: Introductionmentioning
confidence: 99%
“…Oleogels have been studied for over 10 years as healthy replacements for trans‐ fats since they can be formulated with vegetable oils with no trans‐ fats and low levels of saturated fatty acids (Co & Marangoni, ; Pernetti, van Malssen, Flöter, & Bot, ). Specific application includes the use of oleogels to replace solid fat in ice cream, frankfurters, and baked products (Calligaris, Manzocco, Valoppi, & Nicoli, ; Zetzl, Marangoni, & Barbut, ; Zulim Botega, Marangoni, Smith, & Goff, ). Oleogels are structured oil systems that can be defined as semisolid materials obtained by entrapping liquid oil into a three‐dimensional network.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [25] applied CW oleogels as a shortening replacer to prepare cookies. Waxes have also been applied in ice cream [28] and in confectionary fillings. Yilmaz and € O guẗcü [ 26] also studied the applicability of wax-based oleogels in cookies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that monoglycerides rich in oleic acid (GMU) enhance aggregation of solid fat globules resulting in a firmer structure in terms of high storage modulus (Granger, Leger, Barey, Langendorff, & Cansell, ; Méndez‐Velasco & Goff, ; Munk et al., ). Also in oleogel‐based ice cream GMU has been found to increase fat destabilization which caused slower meltdown rate of ice cream (Zulim Botega et al., ). This effect on fat globule aggregation was the reason for selecting GMU as emulsifier in present study.…”
Section: Resultsmentioning
confidence: 99%
“…Application of oleogels in low saturated ice cream has previously been attempted. Zulim Botega, Marangoni, Smith, and Goff (, ) applied sunflower oil oleogels structured by rice bran wax, candelilla wax and carnauba wax to replace crystalline fat in ice creams. Rice bran wax resulted in the highest structural stability in terms of ice cream shape retention and low meltdown rate.…”
Section: Introductionmentioning
confidence: 99%